2020
DOI: 10.1158/1535-7163.mct-19-0841
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Inhibition of Focal Adhesion Kinase and BCL-2 Enhances Antileukemia Activity of Venetoclax in Acute Myeloid Leukemia

Abstract: Focal adhesion kinase (FAK) promotes cancer cell growth and metastasis. We previously reported that FAK inhibition by the selective inhibitor VS-4718 exerted antileukemia activities in acute myeloid leukemia (AML). The mechanisms involved, and whether VS-4718 potentiates efficacy of other therapeutic agents, have not been investigated. Resistance to apoptosis inducted by the BCL-2 inhibitor in AML is mediated by preexisting and ABT-199-induced overexpression of MCL-1 and BCL-XL. We observed that VS-4718 or si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Mcl-1 are also downstream of PI3K/AKT pathway, which are frequently constitutively activated in AML [9,48] The PI3K/AKT signaling pathway plays a key role in tumor occurrence, development and radiation resistance; is involved in various cellular activities and metabolic regulation; and is closely related to the proliferation and apoptosis, cell cycle regulation, angiogenesis and invasion and metastasis of cancer cells. The PI3K/AKT pathway inhibits apoptosis through a variety of mechanisms [49] .…”
Section: The Possible Reason Is That the Binding Of Mcl-1 And Bim Increases The Stability Of Mcl-1 Protein The Sequestration Of Bim Bymentioning
confidence: 99%
See 2 more Smart Citations
“…Mcl-1 are also downstream of PI3K/AKT pathway, which are frequently constitutively activated in AML [9,48] The PI3K/AKT signaling pathway plays a key role in tumor occurrence, development and radiation resistance; is involved in various cellular activities and metabolic regulation; and is closely related to the proliferation and apoptosis, cell cycle regulation, angiogenesis and invasion and metastasis of cancer cells. The PI3K/AKT pathway inhibits apoptosis through a variety of mechanisms [49] .…”
Section: The Possible Reason Is That the Binding Of Mcl-1 And Bim Increases The Stability Of Mcl-1 Protein The Sequestration Of Bim Bymentioning
confidence: 99%
“…The 5-year overall survival rate of AML is only approximately 25% [4] . Pre-clinical and clinical studies have demonstrated that the selective and highly potent Bcl-2 inhibitor venetoclax has anti-leukemia activities against various hematological malignancies, including MDS, CLL, and AML [5][6][7][8][9] . Venetoclax is FDA approved for a subset of patients with CLL and AML [10,11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical and clinical studies have demonstrated that the selective and highly potent Bcl-2 inhibitor venetoclax has anti-leukemia activities against various hematological malignancies, including myelodysplastic syndrome (MDS), chronic lymphocytic leukemia (CLL), and AML (4)(5)(6)(7)(8). Venetoclax is FDA approved for a subset of patients with CLL and AML (9,10), and the FDA-approved combination of venetoclax with decitabine or azacitidine is resulting in CR/complete response with incomplete hematologic recovery (CRi) rates of 70-95% and good tolerability in elderly AML patients, although patients invariably relapse (8,11,12). Resistance to apoptosis inducted by venetoclax in AML is mediated by pre-existing and venetoclax-induced overexpression of Mcl-1 (8), and the overexpression of Mcl-1 has been reported in AML at relapse (13).…”
Section: Introductionmentioning
confidence: 99%
“…Venetoclax is FDA approved for a subset of patients with CLL and AML (9,10), and the FDA-approved combination of venetoclax with decitabine or azacitidine is resulting in CR/complete response with incomplete hematologic recovery (CRi) rates of 70-95% and good tolerability in elderly AML patients, although patients invariably relapse (8,11,12). Resistance to apoptosis inducted by venetoclax in AML is mediated by pre-existing and venetoclax-induced overexpression of Mcl-1 (8), and the overexpression of Mcl-1 has been reported in AML at relapse (13). The mechanism by which Mcl-1 blocks the progression of apoptosis is through binding and sequestering the pro-apoptotic BH3-only proteins Bim, PUMA, Noxa, Bak, and Bax (14), preventing pore formation on the mitochondrial membrane and the release of cytochrome c into the cytoplasm (15).…”
Section: Introductionmentioning
confidence: 99%